The Effects of Suction/Injection and Chemical Reaction on The Flow of Mass Transfer of A Micro Polar Fluid Past A Continuously Moving Plate in the Presence of Magnetic Field. - Shaban, Samia Sayed (JOURNAL OF ADVANCES IN PHYSICS, 2020)
An analysis is carried out to study the effects of chemical reaction and suction /injection on the flow of a micro polar fluid past a moving plate in the presence of magnetic field and mass transfer. The boundary layer equations are transformed to non-linear ordinary differential equations. Numerical results are presented for the distribution velocity, micro rotation profiles within the boundary layer. The effects of varying magnetic parameter, the non-dimensional chemical reaction parameter , Schmidt number, porosity parameter, micro rotation parameter, and coupling constant parameter are revealed.